Principals Leadership in Improving Students Entrepreneurial Competence - Finorina, Finorina; Rahman, Saifur; Alam, Iskandar Ali; Barusman, Andala Rama Putra; Habiburrahman, Habiburrahman (Universitas Batanghari, 2024)
The problem of imbalance between the number of labor force growth and available jobs is a seriousconcern in the context of education and economic development today. The phenomenon where the number of Vocational High School (SMK) graduates continues to grow but their ability to become entrepreneurs or create new jobs is still minimal highlights the importance of effective entrepreneurship education. Currently, entrepreneurship education in schools tends to only touch the surface, focusing on introducing entrepreneurial values, without giving emphasis on internalizing these values or encouraging real actions in daily life. Based on these problems, this paper will discuss how the principal's leadership and how the principal's leadership strategy in improving student entrepreneurship in SMK. The research process using literature study begins with the identification of the topic or research question to be researched. After that, researchers search for related literature through various sources of information such as libraries, online databases, and electronic journals. With great responsibility, school principals are responsible for the implementation of learning activities that can ultimately improve existing graduates, especially in the field of entrepreneurship. In line with this, some of the strategies that can be carried out by school principals in improving student entrepreneurial competence are by creating innovation, working hard in improving school quality, motivation, never giving up, and having entrepreneurial instincts.